The psychological conditions of children and youth in Lebanon after the July 2006 war - El Amine, Adnan (Beirut Lebanese Association for Educational Sciences; Kuwait Society for the advancement of Arab, 2008)
This book treats several questions related to the psychological conditions of children and youth in Lebanon after the July 2006 War. The first chapter explain the used methodology for the study. The second chapter treats the types of exposure to the Lebanese-Israeli War of July-August 2006 in the eyes of youth, children and their parents, the third chapter explain the post-traumatic stress, anxiety and perceived stress by the children and youth. The last three chapter treats the students mental health from preschool to grade 12.
: Book
Keywords: Guerre; Psychological Health; Santé psychologique; War; 2006